INTEGRATION OF TECHNOLOGY IN ISLAMIC EDUCATION: FIQH DISCOURSE ON THE USE OF ARTIFICIAL INTELLIGENCE (AI) IN RELIGIOUS LEARNING - La Zubair; Isroqunnajah (Fiqhuna: Jurnal Pendidikan Agama Islam, 2025)
The development of Artificial Intelligence (AI) technology has brought significant changes in various sectors of life, including in the education sector, especially in religious learning. So it is necessary to study Islamic law in the use of this technology. This study aims to explore and analyze Islamic law studies on the use of AI in religious learning. Using a qualitative approach with a literature review method, this study analyzes the concept of Islamic law related to AI in Islamic education, as well as reviews relevant literature and regulations. The results of the study show that the law on the use of AI in religious learning is contextual, depending on the intention, purpose, method of use, and its impact on Islamic values. However, in general the use of AI is permitted, this is based on the opinions of scholars both classical and contemporary. So AI can be used in religious learning, but still within the limits of sharia. Thus this study emphasizes the importance of understanding the implications of Islamic law on AI, in order to be wise and responsible in its use in religious learning.